The efficacy of systemic glucocorticosteroids for pain in rheumatoid arthritis: a systematic literature review and meta-analysis. (2nd July 2021) - McWilliams, Daniel F; Thankaraj, Divya; Jones-Diette, Julie; Morgan, Rheinallt; Ifesemen, Onosi S; Shenker, Nicholas G; Walsh, David A
Abstract: Objectives: Glucocorticosteroids (GCs) are recommended to suppress inflammation in people with active RA. This systematic review and meta-analysis aimed to quantify the effects of systemic GCs on RA pain. Methods: A systematic literature review of randomized controlled trials (RCTs) in RA comparing systemic GCs to inactive treatment. Three databases were and spontaneous pain and evoked pain outcomes were extracted. Standardized mean differences (SMDs) and mean differences were meta-analysed. Heterogeneity ( I 2, tau statistics) and bias (funnel plot, Egger's test) were assessed. Subgroup analyses investigated sources of variation. This study was pre-registered (PROSPERO CRD42019111562). Results: A total of 18 903 titles, 880 abstracts and 226 full texts were assessed. Thirty-three RCTs suitable for the meta-analysis included 3123 participants. Pain scores (spontaneous pain) decreased in participants treated with oral GCs; SMD = −0.65 (15 studies, 95% CI −0.82, −0.49, P <0.001) with significant heterogeneity ( I 2  = 56%, P =0.0002). Efficacy displayed time-related decreases after GC initiation. Mean difference visual analogue scale pain was −15 mm (95% CI −20, −9) greater improvement in GC than control at ≤3 months, −8 mm (95% CI −12, −3) at >3–6 months and −7 mm (95% CI −13, 0) at >6 months. Similar findings were obtained when evoked pain outcomes were examined. Data from five RCTs suggested improvement also in fatigue during GC treatment. Conclusion: Oral GCs are analgesic in RA. The benefit is greatest shortly after initiation and GCs might not achieve clinically important pain relief beyond 3 months. Treatments other than anti-inflammatory GCs should be considered to reduce the long-term burden of pain in RA.